2013
DOI: 10.11604/pamj.2013.16.63.1407
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of community health workers to the control of Buruli ulcer in the Ngoantet area, Cameroon

Abstract: IntroductionBuruli ulcer (BU) is a skin disease caused by Mycobacterium ulcerans. It is the third most common mycobacterial infection after tuberculosis and leprosy. Community Health Workers (CHWs) hold the potential to support patients and their families at the community level.MethodsWe conducted a cross-sectional descriptive study to assess the participation of CHWs in the early diagnosis and treatment of BU in Ngoantet, Cameroon. The CHWs performance was measured using: the number of cases referred to the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
1
10
1
Order By: Relevance
“…It is the same for the reference case by CHWs with 73.1% in Bénin and 84.2% in Togo. This rate of 95% reported by the study conducted by Vouking et al in Cameroon in 2013 is higher than those found in our study [25]. This difference is explained by the activities in question.…”
Section: The Role Of Community Health Agentscontrasting
confidence: 72%
See 1 more Smart Citation
“…It is the same for the reference case by CHWs with 73.1% in Bénin and 84.2% in Togo. This rate of 95% reported by the study conducted by Vouking et al in Cameroon in 2013 is higher than those found in our study [25]. This difference is explained by the activities in question.…”
Section: The Role Of Community Health Agentscontrasting
confidence: 72%
“…This may also explain the acquisition of knowledge to an acceptable level of household heads. Vouking et al also reached in an evaluation of the participation of community health workers in the early diagnosis and treatment of Buruli ulcer Ngoantet, Cameroonin 2013 to demonstrate the role played by the CHWs through home visits [25]. This observation was also made by Pati et al in an intervention where community health workers through home visits were successful in increasing infants' immunization rates [26].…”
Section: The Role Of Community Health Agentsmentioning
confidence: 89%
“…This is the first study addressing the role of community health volunteers in the control of BU in Benin. Few studies address the role of CHW in BU detection worldwide [18] , [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm the impact of community health volunteers on the control of BU. The use of community health workers for BU control in countries other than Benin has been suggested [27] and also discussed in a review based on sparsely available data on their performance and training [18] .…”
Section: Discussionmentioning
confidence: 99%
“…9 Early detection of cases seems to be of vital importance and could, together with standardized drug treatment, drastically reduce the need for hospitalization and surgery. There are indications that community-based surveillance volunteers (CBSVs) can be effective in the early referral of BU cases, 11 but solid evidence is lacking. 12 Here, we report on the early detection activities of the BU Clinic in Agogo in the Ashanti region of Ghana, where recent advances in diagnosis and treatment of BU have been implemented and combined with rigorous public health efforts aimed at early detection and decentralized care.…”
mentioning
confidence: 99%